Studi kepemimpinan manajerial dalam perspektif islam: Survey pengaruh profil pengasuh lembaga dan profil kepemimpinan terhadap penentuan kebijakan organisasi dengan variabel mediasi partisipasi jamaah pada Pondok Pesantren Riyadlul Jannah Pacet Mojokerto - Budiyono Santoso (FADZAT: Jurnal Ekonomi Syariah, 2020)
Islamic perspective managerial leadership contains at least three basic elements of organization, leader and Jamaah. The leader takes the decision in consultation with the congregation. Jamaah dynamic in participation and action brings the process of Islamic leadership in a positive direction because it acts as an observer, cooperative with its leaders. provide their leaders with the necessary advice so as to contribute to decision making. They also warned against inappropriate actions, withdrawing their support if the leader deviates from the Islamic shari'a rules of the Koran, Hadith, Izma and Qias. Leaders and congregations are responsible to the organization to achieve worldly prosperity and eternal happiness with the ultimate goal of achieving the good pleasure of Allah (Swt) through the fulfillment of the rational goals of the organization (halal). The objectives of this study are: 1) To analyze the profile of institutional caregivers that have a significant effect on congregational participation; 2) Analyzing the leadership profile has a significant effect on congregational participation; 3) Analyzing congregational participation has a significant effect on the determination of organizational policy; 4) Analyzing the profile of institutional caregivers has a significant effect on the determination of organizational policy; 5) To analyze the leadership profile has a significant effect on the determination of organizational policy; 6) Analyzing the profile of institutional caregivers and leadership profiles have a significant effect on the determination of organizational policy through the mediating variable of congregational participation. This research is an explanatory research. The sample used was 91 people as respondents at the Riyadlul Jannah Pacet Mojokerto Islamic Boarding School Jamaah, the respondents returned the questionnaire filling for 48 people, the way of data collection was a questionnaire. The statistical analysis used is multiple linear regression analysis. The calculation of the estimated value of the variables was carried out with the help of the SPSS version 26 program. From the results of the study it can be concluded as follows: 1) The profile of the institution's caretaker does not have a significant effect on congregational participation. 2) The leadership profile has a significant effect on congregational participation. 3) The profile of the institution's carer does not have a significant effect on the determination of organizational policy. 4) The leadership profile has no significant effect on the determination of organizational policy. 5) The participation of the congregation has no significant effect on determining organizational policy. 6) The profile of institutional caregivers and leadership profiles have a significant effect on the determination of organizational policy through the variable of congregational participation.